Local people’s interaction with Wejig-Mahgo-Waren Massif Forest in Southern Tigray, Ethiopia - Mebrahtu Hishe; Mirutse Giday; Zemede Asfaw; Sebsebe Demissew; Bikila Warkineh (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Ethiopia is home to a rich diversity of traditional knowledge and practices, including the use of medicinal plants for healthcare. This study investigates the ethnobotanical knowledge and use of medicinal plants among communities residing near the Wejig-Mahgo-Waren Massif Forest in Southern Tigray, Ethiopia, and compares these findings with the broader Ethiopian ethnobotanical database. Methods Data were collected through semi-structured interviews with 309 randomly selected informants and 30 key informants. Ethnobotanical analytical tools, including preference ranking, informant consensus factor (ICF), and fidelity level (FL), were employed. A comparative analysis was conducted with the Ethiopian ethnobotanical database to assess novel reports and commonalities across regions. Results Fifty-two plant species were documented for treating human and livestock ailments. The study revealed significant differences in medicinal plant knowledge among social groups, with men, older individuals, and illiterate informants demonstrating greater knowledge. A comparative analysis with the Ethiopian ethnobotanical database highlighted both commonalities and unique uses of medicinal plants in the study area. The study shares a 51.6% similarity index with previous Ethiopian ethnobotanical studies. However, livestock medicinal plant similarity is low (7.9%), indicating highly localized ethnoveterinary practices. Dermatological diseases scored the highest ICF value (0.98), and Verbascum sinaiticum had the highest FL (96.15%). Conclusion The study underscores the critical role of the Wejig-Mahgo-Waren Massif Forest in supporting traditional medical practices. The findings highlight the need for conservation and scientific validation of these medicinal plants to ensure their sustainability and benefits for future generations. The comparative analysis provides valuable insights into the ethnobotanical practices across Ethiopia, emphasizing the importance of cross-cultural interpretations in ethnobotanical research.